Comparison of internalizing and externalizing problems in inattentive and combined subtypes of attention deficit / hyperactivity disorder - Reza Rostami; samaneh Farahani; Fatemeh Dehghani Arani (مجله علوم روانشناختی, 2021)
Background: Many studies have looked at the adverse effects of attention deficit / hyperactivity disorder and especially its comorbidity with other disorders. However, the findings of these disorders are contradictory and on the other hand, there is a research gap in the field of compound subgroups and also there is no study in this field considering the Iranian culture. Aims: The purpose of the present study was to investigate comparison of the internalizing and externalizing behavior problems in inattentive and combined subtypes of attention deficit / hyperactivity disorder. Method: The present study was of causal-comparative type. The statistical population of the present study included children with attention deficit / hyperactivity disorder who referred to Atieh Clinic in Tehran in 2016, of which 118 children included 28 girls and 30 boys in the inattentive subgroup and 30 girls and 30 boys in combined subgroup, were selected in available way. Under the compound group were selected in an accessible manner. Subjects were examined with Continuous Performance Test (1956), and Child Behavior Checklist (1991). Data were analyzed using two-way analysis of variance. Results: The results showed that the internalizing behavior problems and externalizing behavior problems are mostly overlooked in the subgroup of inattentive and the combined, respectively. Also, the internalizing behavior problems in girls were higher than that of boys. Conclusions: Based on the findings of this study, it seems that in each subgroup of attention deficit / hyperactivity disorder and in girls and boys, the behavioral problems of internalization and externalization are different and therefore need to be addressed. They have special interventions.